Sustainable production of Saussurea costus under different levels of nitrogen, phosphorus and potassium fertilizers in cold desert region of Western Himalaya - Vishvamitera, Sakshi; Dhiman, Diksha; Baghla, Sidharth; Singh, Satbeer; Kumar, Manish; Kumar, Ashok; Kumar, Dinesh; Singh, Sanatsujat; Chauhan, Ramesh (Frontiers in Plant Science, 2023)
Saussurea costus, an important critically endangered medicinal herb native to the Himalayan region, is commonly used in various ailments, viz. asthma, ulcer, inflammation, and stomach problems. In the international market, the dry roots and essential oil of S. costus has become an important drug. The lack of appropriate fertilizer dose recommendations is one of the limiting factors for its ex-situ conservation and large-scale cultivation, as plant nutrition is vital in determining crop growth and productivity. The study aimed to understand the comparative impact of different levels of fertilizer nutrients on the growth, dry root and essential oil yield, and essential oil profile of costus. Therefore, a field experiment was conducted in Himachal Pradesh, India's cold desert region (Lahaul valley), during 2020-21. The experiment comprised three levels of nitrogen (60, 90, and 120 kg ha-1), three levels of phosphorus (20, 40, 60 kg ha-1), and two levels of potassium (20 and 40 kg ha-1) in a factorial randomized block design. The fertilizer application had an immense effect on the growth attributes, root yield attributes, dry root yield, and essential oil yield over control. The treatment combination N120, P60, and K40 had the largest effect on the plant height, number of leaves per plant, leaf length and width, root length and diameter, dry matter per plant, dry root yield, and essential oil yield. However, the results were at par with the treatment comprising N90, P40, and K20. Dry root yield increased by 108.9%, and essential oil yield increased by 210.3% with fertilizer applications over unfertilized plots. The regression curve shows an increasing trend in dry root yield till N90, P40, and K20; after that, it nearly stabilized. The heat map showed that applying fertilizer significantly affected the chemical constituents of costus essential oil. Similarly, the plots fertilized with the highest level of NPK recorded the utmost value of available N, P, and K, as compared to unfertilized plots. The results emphasize that for sustainable cultivation of S. costus, the application of N90, P40, and K20 combinations is the most suitable one.